Expanding PAM recognition and enhancing base editing activity of Cas9 variants with non‐PI domain mutations derived from xCas9. (24th April 2022) - Xie, Lifang; Hu, Yun; Li, Li; Jiang, Lurong; Jiao, Yaoge; Wang, Yanhong; Zhou, Lifang; Tao, Rui; Qu, Junyan; Chen, Qiang; Yao, Shaohua
Abstract : The recognition of protospacer adjacent motif (PAM) is a key factor for the CRISPR (i.e. clustered regularly interspaced short palindromic repeats)/CRISPR‐associated 9 (Cas9) system to distinguish foreign DNAs from the host genome, and also significantly restricts the targeting scope of the system during genome‐editing applications. Structurally, the PAM interacting (PI) domain, which usually is located in the C‐terminus of Cas9 proteins, directly binds to PAM and plays a key role in determining the recognition specificity. However, several lines of evidence showed that other regions of Cas9 protein beyond the PI domain might also play roles in PAM interaction. Here, we constructed a mosaic SpCas9 protein (xCas9‐NG) by fusing the PI domain of SpCas9 PAM variant, Cas9‐NG with the non‐PI fragment of xCas9 protein that contains multiple amino acid substitutions. We found that non‐PI fragment of xCas9 expanded PAM recognition of the Cas9‐NG PI domain. In addition, xCas9‐NG showed an improved editing efficiency in the majority of targets harboring xCas9 and Cas9‐NG PAMs. Importantly, this finding was also successfully extended to other Cas9 variants, including SpRY and the non‐G SpCas9 series. Together, our work expands the target scope of SpCas9 editing system and demonstrates the notion that the non‐PI domain fragment plays an important role in PAM restriction. Abstract : Protospacer adjacent motif (PAM) recognition is crucial for the CRISPR/Cas9 system. The PAM‐interacting (PI) domain of Cas9 binds to PAM, determining the recognition specificity. However, additional Cas9 regions might affect PAM interaction. Here, Shaohua Yao and colleagues fused the PI domain of Cas9‐NG with a non‐PI fragment of xCas9, producing the mosaic xCas9‐NG, and found that the non‐PI fragment of xCas9 enhances PAM recognition of the Cas9‐NG PI domain. xCas9‐NG shows improved editing efficiency in targets harboring xCas9 and Cas9‐NG PAMs. This work broadens the target scope of Cas9‐based editing and demonstrates the importance of the non‐PI fragment in PAM restriction.